Effectiveness Of Oxytocin Massage And Effleurage Massage On The Volume Of Breast Milk In Primipara - Sehmawati; Dewi Setyobudii (LPPM AN NUUR, 2022)
Background: Mother's milk (ASI) is the only source of natural nutrients produced by humans, breast milk contains a good nutritional composition and contains non-nutritive bioactive components that function for development. Breast milk can save the lives of more than 820,000 children under 5 years of age each year, the majority 87%, especially babies under 6 months of age. Objective: to determine the effectiveness of oxytocin massage and efflurage massage on the milk volume of primiparous postpartum mothers. This research method uses a quasi-experimental type, a research design with two groups (Oxytocin massage group and Effleurage Massage group) pre-test post-test design, to determine the effect of oxytocin massage and Effleurage massage on increasing the volume of breast milk in primiparous postpartum mothers. Sampling with non-probability sampling technique obtained a total sample of 34 respondents. Methods of data analysis using non-parametric static analysis techniques Wilcoxon and Mann Whitney with α 0.05. Results: From the results of the study on 17 respondents, the results showed that there were differences in the pretest and posttest in the oxytocin massage and efflurage massage groups, namely an increase in milk production after treatment, namely there was a difference in the mean pretest and mean posttest with the result P = 0.001 < α 0.05. Conclusion: From the results of the study on 34 respondents there was an effect of Oxytocin massage and Effleurage massage on increasing milk production in postpartum mothers